2015
DOI: 10.1371/journal.pone.0120411
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Circulating Complement Proteins and Cutaneous Microvascular Endothelial Cells in the Development of Childhood Henoch-Schönlein Purpura

Abstract: ObjectiveIn addition to IgA, the deposition of complement (C)3 in dermal vessels is commonly found in Henoch-Schönlein purpura (HSP). The aim of this study is to elucidate the role of circulating complement proteins in the pathogenesis of childhood HSP.MethodsPlasma levels of C3a, C4a, C5a, and Bb in 30 HSP patients and 30 healthy controls were detected by enzyme-linked immunosorbent assay (ELISA). The expression of C3a receptor (C3aR), C5a receptor (CD88), E-selectin, intercellular adhesion molecule 1 (ICAM-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…It is a much more common diagnosis in children younger than 10 years, with mean age 6 years old, as found in the great majority of literature on this subject. [1][2][3][4][5][6][7] There have been some studies describing equal incidence between genders, similar to what we have found. 6 There was an upper airway infection in more than half of the cases, consistent with it being the most commonly pointed trigger.…”
Section: Discussionsupporting
confidence: 82%
“…It is a much more common diagnosis in children younger than 10 years, with mean age 6 years old, as found in the great majority of literature on this subject. [1][2][3][4][5][6][7] There have been some studies describing equal incidence between genders, similar to what we have found. 6 There was an upper airway infection in more than half of the cases, consistent with it being the most commonly pointed trigger.…”
Section: Discussionsupporting
confidence: 82%
“…More than 90% of patients are under 10 years of age, with a mean age of 6 years (1,2). HSP is a leukocytoclastic vasculitis involving small vessels (3). Its clinical presentation includes cutaneous palpable purpura, joint pain, renal involvement, colicky abdominal pain and gastrointestinal bleeding.…”
mentioning
confidence: 99%
“…In our review it was difficult to make a comparison with these results, since most of our patients had no immunoglobulin analytical data, and in the 6 patients with the data only 2 showed elevated levels. It has also been reported that complement activation by alternative pathways could be related to IgAV pathogenesis, which would be reflected by higher serum levels of these proteins in affected patients [12]. In our review, data concerning this point were collected for only 5 patients, and one case showed a reduction of serum complement levels.…”
Section: Discussionmentioning
confidence: 95%